Detection and molecular characterisation of bovine Enterovirus in Brazil: Four decades since the first report - Candido, M.; Almeida-Queiroz, S. R.; Buzinaro, M. G. [UNESP]; Livonesi, M. C.; Fernandes, A. M.; Sousa, R. L.M. (Cambridge University Press (CUP), 2019)
It is suggested that bovine enteroviruses (BEV) are involved in the aetiology of enteric infections, respiratory disease, reproductive disorders and infertility. In this study, bovine faecal samples collected in different Brazilian states were subjected to RNA extraction, reverse transcription-polymerase chain reaction analysis and partial sequencing of the 5′-terminal portion of BEV. One hundred and three samples were tested with an overall positivity of 14.5%. Phylogenetic analysis clustered these BEV Brazilian samples into the Enterovirus F clade. Our results bring an important update of the virus presence in Brazil and contribute to a better understanding of the distribution and characterisation of BEV in cattle.
Keywords: Animal viruses; Bovine enterovirus; Cattle diseases; Molecular diagnostics